Ultrahigh-fluidity grouting material as well as preparation method and application thereof
By combining an inorganic synergistic system of nano-sol and high CEC layered silicate clay with defoamers and expansion agents, the problem of balancing the fluidity and stability of grouting materials has been solved, resulting in a grouting material with ultra-high fluidity, low bleeding rate and high strength, suitable for complex duct construction.
Patent Information
- Application Number
- CN202511341367.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-19
- Publication Date
- 2026-02-06
AI Technical Summary
Existing grouting materials struggle to balance fluidity and stability, rely on organic thickeners leading to performance defects, and have a narrow range of material choices, making it difficult to meet the construction requirements of ultra-long and complex ducts.
An inorganic synergistic system of nano-sol and high CEC layered silicate clay is adopted. The clay structure is optimized by sodium modification and mechanical grinding. Combined with defoamer and calcium sulfoaluminate expansion agent, a grouting material with ultra-high fluidity, excellent stability and high strength is formed.
It achieves ultra-high initial fluidity, low bleeding rate and high strength of slurry at ultra-low water-binder ratio, which is suitable for construction of complex ducts, solves the contradiction between fluidity and stability, reduces material costs and improves construction controllability.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
TECHNICAL FIELD
[0001] The present application belongs to the technical field of building materials, and particularly relates to an ultra-high fluidity pressure grout and a preparation method and application thereof. BACKGROUND
[0002] Post-tensioned prestressed duct grouting is a key process to ensure that the prestressed steel strand is not corroded, effectively bonded with the concrete structure and works together. The quality of the pressure grout is directly related to the durability, safety performance and service life of the overall structure. An excellent pressure grout not only needs to have good workability at the construction stage to ensure full filling in the complex duct, but also should present a microstructure of high density, high strength and low porosity after hardening, so as to ensure the reliable service of the structure within the design life. At present, there is an inherent contradiction in this technical field that the fluidity and stability are difficult to be balanced. In order to adapt to the requirements of pressure grouting construction of ultra-long and complex ducts, the pressure grout needs to have extremely high fluidity, and this performance is often realized by increasing the water-binder ratio or adding a large amount of water reducing agent. However, too high water-binder ratio will lead to an increase in the porosity of the hardened grout, a significant reduction in strength and durability, and more seriously, it will easily cause bleeding and segregation of the grout, resulting in incomplete filling in the duct and forming a hidden danger to the structure safety.
[0003] In the prior art, organic thickeners (such as cellulose ether, polyacrylamide, etc.) or ordinary mineral thickeners (such as bentonite) are usually added to enhance the stability of the grout and inhibit bleeding. However, the use of organic thickeners often accompanies a sharp increase in the viscosity of the grout, an increase in the loss of fluidity over time, and even causes flocculation, which brings difficulties to the construction operation, and may also introduce air bubbles, which weaken the final strength. The dispersion and thixotropic properties of ordinary bentonite are limited due to its low cation exchange capacity (CEC) and insufficient interlayer structure, and the stability effect is not ideal, so a large amount of bentonite is often needed to play a certain role, but this will have an adverse effect on the fluidity and mechanical properties of the grout.
[0004] Therefore, it is an urgent technical problem for those skilled in the art to develop a pressure grout that can realize ultra-high fluidity, excellent stability and high strength at an ultra-low water-binder ratio without relying on organic thickeners. SUMMARY
[0005] One of the purposes of the present application is to provide an ultra-high fluidity pressure grout, which overcomes the problems of the prior art, such as the difficulty in balancing the fluidity and stability of the pressure grout, the performance defects caused by the reliance on organic thickeners, the single function and the narrow range of material selection. The pressure grout of the present application realizes ultra-high fluidity, excellent fluidity retention, almost zero bleeding and high strength at an ultra-low water-binder ratio through the synergistic design of specific components, and does not need to add organic thickeners, so the durability is better.
[0006] The second object of the present application is to provide a preparation method of the super-high fluidity press slurry.
[0007] The third object of the present application is to provide an application of the super-high fluidity press slurry in post-tensioning prestressed structure hole press.
[0008] To achieve the above object, the technical scheme adopted by the present application is as follows: The present application provides a super-high fluidity press slurry, which comprises the following components in parts by weight: Portland cement 40-60 parts, superfine mineral powder 20-30 parts, nano sol 5-8 parts, sodium-modified layered silicate clay or synthetic hectorite 1-3 parts, and polycarboxylic acid water reducer 0.5-1.2 parts; the water-binder ratio of the press slurry is 0.17-0.19, preferably 0.18.
[0009] In some embodiments of the present application, the raw materials of the super-high fluidity press slurry comprise the following components in parts by weight: Portland cement 45-50 parts, superfine mineral powder 25-30 parts, nano sol 6-7 parts, sodium-modified layered silicate clay or synthetic hectorite 1-3 parts, and polycarboxylic acid water reducer 0.5-1.2 parts.
[0010] In some embodiments of the present application, the Portland cement is P・II 52.5 grade or P・O 52.5 grade Portland cement. It has the characteristics of fast strength development, moderate hydration heat, and good stability, and serves as the main cementitious material of the slurry, providing the basis strength of the slurry.
[0011] In some embodiments of the present application, the specific surface area of the superfine mineral powder is ≥1000 m² / kg. Preferably, the superfine mineral powder is S105 grade superfine mineral powder. The main components of the superfine mineral powder are active SiO2 and Al2O3, which can undergo secondary hydration reaction with Ca(OH)2 generated by cement hydration, fill the internal pores of the slurry, improve the density and strength of the slurry, and reduce the hydration heat and shrinkage.
[0012] In some embodiments of the present application, the nano sol comprises at least one of silica sol, alumina sol, and titania sol; the content of SiO2 in the silica sol is 30±2 wt%, and the particle size is 5-10 nm; the content of Al2O3 in the alumina sol is 18-22 wt%, and the particle size is 15-25 nm; the content of TiO2 in the titania sol is 25-30 wt%, and the particle size is 8-15 nm. As a nanoscale dispersed phase, the nano sol has extremely high specific surface area and surface activity, can form uniformly dispersed nanoparticles in the slurry, and can hinder the agglomeration of cementitious material particles through electrostatic repulsion, thereby significantly improving the fluidity of the slurry.
[0013] In some embodiments of the present application, the sodium-modified layered silicate clay is prepared by reacting a layered silicate clay with a sodium salt solution under heating.
[0014] Preferably, the method for preparing the sodium-modified layered silicate clay comprises the following steps: mixing the layered silicate clay with a sodium salt solution, placing it in a reactor, heating and stirring at 60-90°C, and mechanically grinding with a high-speed grinder for 30-60 minutes. After the reaction is completed, the product is filtered, washed until the pH of the filtrate is 7-8, dried, and crushed to obtain the sodium-modified layered silicate clay.
[0015] The layered silicate clay comprises at least one of hectorite and saponite.
[0016] The CEC of the hectorite is 105-120 mmol / 100g, and the CEC of the synthetic saponite is 95-110 mmol / 100g.
[0017] The sodium salt solution comprises at least one of Na2CO3, NaCl, and Na2SiO3, and the mass concentration is 3-8%. The solid-liquid ratio of the layered silicate clay to the sodium salt solution is 1:3-1:5.
[0018] Na2CO3 can replace Ca 2+ , Mg 2+ , and other divalent cations in the clay to form insoluble carbonate precipitates, releasing Na + into the interlayer of the clay to promote interlayer expansion. NaCl can provide a high concentration of Na + to accelerate the ion exchange process. Na2SiO3 not only has a sodium-modifying effect, but also reacts with the hydration products of the cementitious material to improve the strength of the paste.
[0019] In the sodium modification process of the present application, heating and stirring and mechanical grinding are used. Heating can increase the ion diffusion rate and accelerate the ion exchange reaction. Mechanical grinding can destroy the agglomeration structure of the clay and promote the penetration of the modifier into the interlayer, expanding the interlayer spacing of the clay from the original 0.9-1.2 nm to 1.5-2.0 nm and significantly enhancing the thixotropic properties.
[0020] In some embodiments of the present application, the pressure grouting material further comprises a defoaming agent in an amount of 0.01-0.1% based on the total weight of the pressure grouting material. Preferably, the defoaming agent comprises a polyoxypropylene polyoxyethylene ether or an organic silicone defoaming agent. The organic silicone defoaming agent is preferably dimethyl silicone oil.
[0021] The defoaming agent can reduce the surface tension of the liquid, destroy the bubble film generated during stirring, cause the bubbles to burst and escape, effectively reduce the air content of the paste (controlled below 2%), and improve the density and bonding strength of the paste.
[0022] In some embodiments of the present application, the press slurry further comprises a calcium sulphoaluminate type expansive agent, which accounts for 0.5-2% of the total weight of the press slurry. The specific surface area of the calcium sulphoaluminate type expansive agent is 400-500 m² / kg, and its main component is calcium sulphoaluminate (C4A3S), which can react with gypsum to generate ettringite in the hydration process, and the molecular formula of ettringite is 3CaO·Al2O3·3CaSO4·32H2O. The ettringite crystal is needle-shaped and has a certain volume expansion, which can compensate for the dry shrinkage and cold shrinkage of the slurry, and the 28d limited expansion rate is ≥0.02%, preventing microcracks from appearing at the pore interface.
[0023] The second aspect of the present application discloses a preparation method of the above-mentioned press slurry with ultra-high fluidity, comprising the following steps: S1. Preparing a premixed dry powder: weighing each powdery material according to the proportion, stirring and mixing uniformly to obtain a premixed dry powder; the powdery material comprises Portland cement, ultra-fine mineral powder, sodium-modified layered silicate clay, polycarboxylate superplasticizer, and preferably further comprises a calcium sulphoaluminate type expansive agent; S2. Preparing a mixing liquid containing nanosol: calculating the required amount of mixing water according to the water-binder ratio of the press slurry, then weighing the corresponding proportion of nanosol and adding it to the mixing water, stirring to uniformly disperse the nanosol in the water, and forming a stable mixing liquid containing nanosol; Preferably, the defoaming agent is stirred together with the nanosol; S3. Stirring the premixed dry powder and the mixing liquid containing nanosol uniformly to obtain a press slurry with ultra-high fluidity.
[0024] In some embodiments of the present application, in the step S1, each powdery material is stirred at a speed of 300-500 r / min for 20-40 minutes, and preferably stirred and mixed in a double-shaft stirrer. The paddle design of the double-shaft stirrer can produce strong shear and convection effects, effectively breaking the agglomeration state of dry powder particles, ensuring uniform mixing of each component, and obtaining a premixed dry powder with uniform composition.
[0025] In some embodiments of the present application, in the step S2, the stirring is performed at a speed of 500-800 r / min for 10-15 minutes under a magnetic stirrer. The magnetic stirring drives the stirring rod to rotate through the magnetic field, avoiding direct contact between the mechanical stirring paddle and the liquid, reducing the introduction of air bubbles, while ensuring uniform dispersion of the nanosol in the water, forming a stable mixing liquid containing nanosol, and preventing the agglomeration of nanosol particles.
[0026] In some embodiments of the present application, in step S3, the premixed dry powder is first stirred at a low speed with the mixing liquid containing nanosol to preliminarily fuse the dry powder and the liquid, so as to avoid flying of the dry powder and local caking; and then stirred at a high speed, so as to make the slurry fully dispersed and uniform through high-speed shearing action; preferably, first stirred at 140±5 r / min for 1-2 minutes, and then stirred at 285±10 r / min for 2-3 minutes.
[0027] The third aspect of the present application also discloses application of the super-high-fluidity pressure slurry to hole pressure in post-tensioning prestressed structure.
[0028] Compared with the prior art, the present application has the following beneficial effects: The present application is designed scientifically and ingeniously, and creatively constructs an inorganic synergistic system of "nanosol-high-CEC layered silicate clay", solves the contradiction between fluidity and stability of traditional pressure slurry, and realizes excellent performance under an ultra-low water-binder ratio; the clay is optimized through a deep modification process, a low dosage can achieve a stable effect, the cost is reduced and the strength is improved; functional components are introduced, which can solve engineering problems in a targeted manner and are suitable for various engineering scenes, especially for complex hole pressure construction.
[0029] The inorganic synergistic system of "nanosol-high-CEC layered silicate clay" of the present application effectively improves the performance of the pressure slurry. The nanosol disperses the cementitious material particles through electrostatic repulsion, provides the slurry with super-high initial fluidity, and ensures the smoothness of the construction process. The high-CEC layered silicate clay forms a stable thixotropic structure after sodium modification, which can effectively maintain the stability of the slurry system in the static state of the slurry, avoid bleeding and segregation, and ensure good fluidity of the slurry when it is subjected to shearing action, and ensure the controllability of the construction operation. Relying on the synergistic effect of the above two components, the pressure slurry of the present application can make the slurry achieve the technical indexes of initial fluidity ≥ 30 s, 60 min fluidity basically no loss, bleeding rate nearly zero, and 28 d compressive strength ≥ 75 MPa under the condition of an ultra-low water-binder ratio of 0.18, and completely solves the contradiction that the fluidity and stability of traditional pressure slurry are difficult to balance.
[0030] The present application adopts a deep modification process of sodium treatment and mechanical grinding to optimize and adjust the microstructure of the layered silicate clay, so that the clay layer spacing is expanded from 0.9-1.2 nm in the prior art to 1.5-2.0 nm, thereby greatly enhancing the thixotropic performance of the clay. In actual application, the modified clay only needs to be added to the slurry in a dosage of 1-3 parts, so that the slurry can achieve excellent stability; the problem of fluidity reduction caused by high dosage of traditional mineral thickening agents is avoided, the material cost is reduced, and the slurry strength is improved.
[0031] The pressure slurry also has the advantages of expandable function and wide adaptability. Without affecting the performance of the inorganic synergistic system of the nanosol-high CEC layered silicate clay, by introducing functional components such as a defoaming agent and a calcium sulphoaluminate expanding agent into the slurry, various specific technical problems in engineering practice can be solved. The defoaming agent can control the gas content of the slurry to be below 2%, significantly improve the slurry density, and reduce the performance hidden danger caused by the internal pores of the slurry; the calcium sulphoaluminate expanding agent can make the 28d limited expansion rate of the slurry be greater than or equal to 0.02%, effectively compensate for the shrinkage of the slurry during hardening, and fundamentally prevent cracks in the slurry. With the above expandable functions and excellent performance, the pressure slurry can be applied to different types of engineering scenes such as large-span bridges, high-rise buildings, etc., especially suitable for complex hole pressure grouting construction, and provides reliable material support for high-quality construction of various projects. DETAILED DESCRIPTION
[0032] The following examples are intended to more fully assist in the understanding of the present application, and are not intended to limit the specific embodiments of the present application, nor to limit the technical solutions and protection scope of the present application. It should be particularly pointed out that all products that are the same as or substantially the same as the present application obtained by any person skilled in the art under the inspiration of the present application, or by combining the present application with other prior art features, should be covered within the protection scope of the present application.
[0033] It should be further pointed out that, if the specific experimental steps or conditions are not explicitly recorded in the examples, the conventional experimental steps and conditions recorded in the literature known in the art can be used for implementation; if the reagents and other instruments used in the examples are not specifically marked by the manufacturer, they are all general-purpose reagent products that can be commonly purchased on the market.
[0034] An ultrahigh fluidity pressure slurry, raw materials of which include the following components in parts by weight: 40-60 parts of Portland cement, 20-30 parts of superfine mineral powder, 5-8 parts of nanosol, 1-3 parts of sodium-modified layered silicate clay or synthetic hectorite, and 0.5-1.2 parts of polycarboxylate superplasticizer.
[0035] In some embodiments of the present application, the raw materials of the ultrahigh fluidity pressure slurry include the following components in parts by weight: 45-50 parts of Portland cement, 25-30 parts of superfine mineral powder, 6-7 parts of nanosol, 1-3 parts of sodium-modified layered silicate clay or synthetic hectorite, and 0.5-1.2 parts of polycarboxylate superplasticizer.
[0036] The Portland cement is P・II 52.5 grade or P・O 52.5 grade Portland cement.
[0037] The superfine mineral powder has a specific surface area of greater than or equal to 1000 m² / kg, and is S105 grade superfine mineral powder.
[0038] The nanosol includes at least one of a silica sol, an aluminum sol, and a titanium sol; wherein the silica sol has a SiO2 content of 30±2wt%, and a particle size of 5-10nm; the aluminum sol has an Al2O3 content of 18-22wt%, and a particle size of 15-25nm; and the titanium sol has a TiO2 content of 25-30wt%, and a particle size of 8-15nm.
[0039] The sodium-modified layered silicate clay is prepared by reacting a layered silicate clay with a sodium salt solution under heating. The preparation method comprises the following steps: mixing the layered silicate clay with the sodium salt solution, placing them in a reaction kettle, heating and stirring at 60-90℃, and mechanically grinding with a high-speed grinder for 30-60 minutes. After the reaction is completed, the product is filtered, washed until the pH of the filtrate is 7-8, dried, and crushed to obtain the sodium-modified layered silicate clay. The layered silicate clay includes at least one of hectorite and saponite.
[0040] The CEC of the hectorite is 105-120 mmol / 100g, and the CEC of the synthetic saponite is 95-110 mmol / 100g.
[0041] The sodium salt solution includes at least one of Na2CO3, NaCl, and Na2SiO3, and has a mass concentration of 3-8%. The solid-liquid ratio of the layered silicate clay to the sodium salt solution is 1:3-1:5.
[0042] The pressure grouting material further includes a defoaming agent, which accounts for 0.01-0.1% of the total weight of the pressure grouting material. The defoaming agent includes a polyoxypropylene polyoxyethylene ether or an organic silicon-based defoaming agent. The organic silicon-based defoaming agent is preferably dimethyl silicone oil.
[0043] The pressure grouting material further includes a calcium sulfoaluminate expansive agent, which accounts for 0.5-2% of the total weight of the pressure grouting material. The specific surface area of the calcium sulfoaluminate expansive agent is 400-500m² / kg.
[0044] A preparation method of an ultra-high-fluidity pressure grouting material, comprising the following steps: S1. Preparing a premixed dry powder: weighing each powdery material according to the proportion, placing them in a double-shaft mixer, and stirring at a speed of 300-500r / min for 20-40 minutes to obtain a premixed dry powder; the powdery material includes portland cement, ultra-fine mineral powder, sodium-modified layered silicate clay, and polycarboxylate superplasticizer, and preferably further includes a calcium sulfoaluminate expansive agent; S2. Preparation of nano-sol containing mixing liquid: according to the water-binder ratio of the pressure slurry, the required amount of mixing water is calculated, and then the corresponding proportion of nano-sol is weighed and added to the mixing water. Stir at a speed of 500-800 r / min for 10-15 minutes under a magnetic stirrer to uniformly disperse the nano-sol in water and form a stable nano-sol containing mixing liquid; Preferably, the defoaming agent is stirred with the nano-sol; S3. The pre-mixed dry powder is stirred with the nano-sol containing mixing liquid at 140±5 r / min for 1-2 minutes and then at 285±10 r / min for 2-3 minutes to obtain an ultra-high fluidity pressure slurry. The water-binder ratio of the ultra-high fluidity pressure slurry is 0.17-0.19, preferably 0.18.
[0045] The Portland cement in the embodiment of the present application is P・II 52.5 grade, which meets the GB 175-2007 "General Portland Cement" standard.
[0046] The superfine mineral powder in the embodiment of the present application is S105 grade, with a specific surface area of 1200 m² / kg, an active SiO2 content of 55wt%, and an Al2O3 content of 22wt%.
[0047] The silica sol in the embodiment of the present application has a SiO2 content of 30%, an average particle size of 8 nm, a pH value of 8-9, and a stability of ≥6 months.
[0048] The aluminum sol in the embodiment of the present application has an Al2O3 content of 20%, an average particle size of 20 nm, and a pH value of 4-5.
[0049] The titanium sol in the embodiment of the present application has a TiO2 content of 28%, an average particle size of 12 nm, and a pH value of 3-4.
[0050] The hectorite in the embodiment of the present application has a raw soil CEC=115 mmol / 100g and a particle size of ≤20 μm.
[0051] The synthetic hectorite in the embodiment of the present application has a CEC=100 mmol / 100g and a purity of ≥99%.
[0052] The polycarboxylic acid water reducer in the embodiment of the present application has a solid content of 40%, a water-reducing rate of 40%, and meets the GB 8076-2008 "Concrete Admixture" standard.
[0053] The ordinary bentonite in the embodiment of the present application is a calcium-based bentonite with a CEC=80 mmol / 100g and is commercially available.
[0054] The polyacrylamide (PAM) in the embodiment of the present application has a molecular weight of 8 million, is anionic, and is commercially available.
[0055] The calcium sulphoaluminate expanding agent has a specific surface area of 450 m2 / kg and a 28d limited expansion rate of 0.03%.
[0056] The polyether defoaming agent has an effective component content of 99% and is commercially available.
[0057] Unless otherwise specified, the parts in the embodiments of the present application are mass parts.
[0058] The preparation method of the sodium-modified hectorite in the embodiments of the present application is as follows: 100 parts of hectorite is mixed with 500 parts of a Na2CO3 solution with a concentration of 5 wt%, and is placed in a reaction kettle, stirred at 80 DEG C for 2 hours, and ground by a high-speed grinder (rotating speed of 2000 r / min) for 45 minutes. After the reaction, filtration, washing until the pH value of the filtrate is 7-8, drying at 105 DEG C, and crushing through a 200-mesh sieve, the sodium-modified hectorite with an interlayer spacing of 1.8 nm is obtained.
[0059] The formulations of the press slurry of Examples 1-6 and Comparative Examples 1-3 are shown in Table 1.
[0060] Table 1 Formulations of the press slurry of Examples 1-6 and Comparative Examples 1-3
[0061] In Table 1, the synthetic hectorite is used to replace the modified hectorite in Example 4; 1 part of the expanding agent is added in Example 5; the cement and the mineral powder are adjusted in proportion, and 0.05 parts of the defoaming agent is added in Example 6. Example
[0062] The present embodiment discloses the super-high-fluidity press slurry and the preparation method thereof. The raw material composition of the press slurry of the present embodiment is shown in Table 1: 50 parts of Portland cement, 25 parts of ultra-fine mineral powder, 6 parts of silica sol, 2 parts of sodium-modified hectorite, and 0.8 parts of polycarboxylate superplasticizer.
[0063] The preparation method of the press slurry of the present embodiment is as follows: S1. Preparation of premixed dry powder: the dry powder components are added into a double-shaft mixer, stirred at 400 r / min for 30 minutes to obtain the premixed dry powder; the dry powder components are Portland cement, ultra-fine mineral powder, sodium-modified hectorite, and polycarboxylate superplasticizer.
[0064] S2. Preparation of nano-silica sol-containing mixing liquid: the required amount of mixing water is calculated according to the water-binder ratio of 0.18 of the press slurry, then the corresponding proportion of nano-silica sol is weighed and added into the mixing water, and the nano-silica sol-containing mixing liquid is formed by stirring at 700 r / min for 12 minutes by a magnetic stirrer.
[0065] S3. The premixed dry powder and the mixing liquid are added into a cement neat paste stirrer, and stirred at a low speed (140 r / min) for 1.5 minutes and then at a high speed (285 r / min) for 2.5 minutes, and the water-binder ratio is controlled to be 0.18, to obtain the pressure slurry. Embodiment
[0066] The embodiment discloses a super-high-fluidity pressure slurry and a preparation method thereof. Raw material composition of the pressure slurry in the embodiment is shown in Table 1: 50 parts of Portland cement, 25 parts of superfine mineral powder, 6 parts of aluminum sol, 2 parts of sodium-modified hectorite, and 0.8 parts of polycarboxylate superplasticizer.
[0067] The preparation method of the pressure slurry in the embodiment is as follows: S1. A premixed dry powder is prepared by adding dry powder components into a double-shaft stirrer and stirring at 400 r / min for 30 minutes; the dry powder components are Portland cement, superfine mineral powder, sodium-modified hectorite, and polycarboxylate superplasticizer.
[0068] S2. A mixing liquid containing nano sol is prepared by calculating the required amount of mixing water according to the water-binder ratio 0.18 of the pressure slurry, then adding the corresponding proportion of nano aluminum sol into the mixing water, and stirring at 700 r / min for 12 minutes by a magnetic stirrer to form the mixing liquid containing nano sol.
[0069] S3. The premixed dry powder and the mixing liquid are added into a cement neat paste stirrer, and stirred at a low speed (140 r / min) for 1.5 minutes and then at a high speed (285 r / min) for 2.5 minutes, and the water-binder ratio is controlled to be 0.18, to obtain the pressure slurry. Embodiment
[0070] The embodiment discloses a super-high-fluidity pressure slurry and a preparation method thereof. Raw material composition of the pressure slurry in the embodiment is shown in Table 1: 50 parts of Portland cement, 25 parts of superfine mineral powder, 6 parts of aluminum sol, 2 parts of sodium-modified hectorite, and 0.8 parts of polycarboxylate superplasticizer.
[0071] The preparation method of the pressure slurry in the embodiment is as follows: S1. A premixed dry powder is prepared by adding dry powder components into a double-shaft stirrer and stirring at 400 r / min for 30 minutes; the dry powder components are Portland cement, superfine mineral powder, sodium-modified hectorite, and polycarboxylate superplasticizer.
[0072] S2. A mixing liquid containing nano sol is prepared by calculating the required amount of mixing water according to the water-binder ratio 0.18 of the pressure slurry, then adding the corresponding proportion of nano aluminum sol into the mixing water, and stirring at 700 r / min for 12 minutes by a magnetic stirrer to form the mixing liquid containing nano sol.
[0073] S3. The premixed dry powder and the mixing liquid are added into a cement net paste stirrer, and stirred at a low speed (140 r / min) for 1.5 minutes and then at a high speed (285 r / min) for 2.5 minutes, and the water-binder ratio is controlled to be 0.18, to obtain the pressure slurry. Embodiment
[0074] The embodiment discloses a super-high-fluidity pressure slurry and a preparation method thereof. The raw material composition of the pressure slurry is shown in Table 1: 50 parts of Portland cement, 25 parts of superfine mineral powder, 6 parts of silica sol, 2 parts of synthetic hectorite, and 0.8 parts of polycarboxylic acid water reducer.
[0075] The preparation method of the pressure slurry is as follows: S1. A premixed dry powder is prepared by adding dry powder components into a double-shaft stirrer and stirring at 400 r / min for 30 minutes; the dry powder components are Portland cement, superfine mineral powder, synthetic hectorite and polycarboxylic acid water reducer.
[0076] S2. A mixing liquid containing nano sol is prepared by calculating the required amount of mixing water according to the water-binder ratio 0.18 of the pressure slurry, then adding the corresponding proportion of nano silica sol into the mixing water, and stirring at 700 r / min for 12 minutes by a magnetic stirrer to form the mixing liquid containing nano sol.
[0077] S3. The premixed dry powder and the mixing liquid are added into a cement net paste stirrer, and stirred at a low speed (140 r / min) for 1.5 minutes and then at a high speed (285 r / min) for 2.5 minutes, and the water-binder ratio is controlled to be 0.18, to obtain the pressure slurry. Embodiment
[0078] The embodiment discloses a super-high-fluidity pressure slurry and a preparation method thereof. The raw material composition of the pressure slurry is shown in Table 1: 50 parts of Portland cement, 25 parts of superfine mineral powder, 6 parts of silica sol, 2 parts of synthetic hectorite, and 0.8 parts of polycarboxylic acid water reducer.
[0079] The preparation method of the pressure slurry is as follows: S1. A premixed dry powder is prepared by adding dry powder components into a double-shaft stirrer and stirring at 400 r / min for 30 minutes; the dry powder components are Portland cement, superfine mineral powder, synthetic hectorite and polycarboxylic acid water reducer.
[0080] S2. A mixing liquid containing nano sol is prepared by calculating the required amount of mixing water according to the water-binder ratio 0.18 of the pressure slurry, then adding the corresponding proportion of nano silica sol into the mixing water, and stirring at 700 r / min for 12 minutes by a magnetic stirrer to form the mixing liquid containing nano sol.
[0081] S3. The premixed dry powder and the mixing liquid are added to the cement neat paste stirrer, first stirring at low speed (140 r / min) for 1.5 minutes, then stirring at high speed (285 r / min) for 2.5 minutes, and the water-binder ratio is controlled to be 0.18, to obtain the pressure grouting material. Example
[0082] The present example discloses a super-high-fluidity pressure grouting material and a preparation method thereof. The raw material composition of the pressure grouting material of the present example is shown in Table 1: 45 parts of Portland cement, 30 parts of superfine mineral powder, 7 parts of silica sol, 2 parts of sodium-modified hectorite, 1.0 parts of polycarboxylate superplasticizer, and 0.05 parts of sulfur polyether defoaming agent.
[0083] The preparation method of the pressure grouting material of the present example is as follows: S1. Preparation of premixed dry powder: the dry powder components are added to a double-shaft stirrer, and stirred at 400 r / min for 30 minutes to obtain the premixed dry powder; the dry powder components are Portland cement, superfine mineral powder, sodium-modified hectorite, polycarboxylate superplasticizer, and calcium aluminate sulfate expanding agent.
[0084] S2. Preparation of nano-sol-containing mixing liquid: the required amount of mixing water is calculated according to the water-binder ratio 0.18 of the pressure grouting material, then the corresponding amount of nano-silica sol is weighed and added to the mixing water, and the nano-sol-containing mixing liquid is formed by stirring at 700 r / min for 12 minutes using a magnetic stirrer.
[0085] S3. The premixed dry powder and the mixing liquid are added to the cement neat paste stirrer, first stirring at low speed (140 r / min) for 1.5 minutes, then stirring at high speed (285 r / min) for 2.5 minutes, and the water-binder ratio is controlled to be 0.18, to obtain the pressure grouting material.
[0086] Comparative Example 1 The formula of the present comparative example 1 is shown in Table 1. Compared with Example 1, there is no modified hectorite in Example 1, and 1.5 parts of ordinary bentonite is additionally added; the rest of the conditions are the same.
[0087] Comparative Example 2 The formula of the present comparative example 2 is shown in Table 1. Compared with Example 1, there is no silica sol and modified hectorite in Example 1, and 2 parts of polyacrylamide is additionally added; the rest of the conditions are the same.
[0088] Comparative Example 3 The formula of the present comparative example 3 is shown in Table 1. Compared with Example 1, there is no silica sol and modified hectorite in Example 1; the rest of the conditions are the same.
[0089] Test Example 1 The performance of the pressure grouting materials of Examples 1-6 and Comparative Examples 1-3 is tested, and the results are shown in Table 2.
[0090] The above examples and comparative examples are detected according to the standard of Technical Specification for Construction of Highway Bridges and Culverts JTG / T 3650-2020.
[0091] Table 2 Performance test results of the grouting materials of examples 1-6 and comparative examples 1-3
[0092] Note: Comparative example 2 cannot be effectively tested for expansion rate and air content due to gelation of the slurry, and comparative example 3 cannot be effectively tested for expansion rate and air content due to serious bleeding segregation.
[0093] As can be seen from Table 2, examples 1-4 of the present application all use the “nanosol-high CEC phyllosilicate clay” synergistic system, which exhibits excellent comprehensive performance: the initial fluidity is 31-35 seconds, the 60 min fluidity is basically no loss, the bleeding rate is ≤0.5%, and the 28-day compressive strength is all ≥79.8 MPa. In contrast, comparative example 3 does not use the synergistic system, its bleeding rate is as high as 4.5%, the 28-day compressive strength is only 65.3 MPa, and the 60 min fluidity drops to 22 seconds, fully proving that the synergistic system of the present application can effectively coordinate the contradiction between fluidity and stability.
[0094] The nanosol of the present application includes silica sol, aluminum sol and titanium sol. As can be seen from Table 2, different types of nanosol of the present application all meet the performance requirements of the grouting material. The grouting material of example 2 using aluminum sol has faster early strength development, with a 28d compressive strength of 81.5 MPa.
[0095] The clay type used in the present application covers synthetic hectorite and sodium-modified phyllosilicate clay. The grouting material performance of example 4 using synthetic hectorite is close to that of example 1 using modified hectorite, indicating that different high CEC clays are suitable for the “nanosol-high CEC phyllosilicate clay” synergistic system of the present application. In addition, synthetic hectorite has higher purity and more stable performance, and is particularly suitable for application scenarios with higher requirements for slurry uniformity.
[0096] As can be seen from example 1 and comparative example 1, the clay modification process of the present application shows significant effect: the grouting material of example 1 using sodium-modified hectorite has a bleeding rate of 0 and a 28-day compressive strength of 80.1 MPa; while the grouting material of comparative example 1 using ordinary bentonite has a bleeding rate of 2.8% and a 28-day compressive strength of only 68.2 MPa. This shows that sodium modification treatment can significantly enhance the stability and strengthening effect of the clay.
[0097] In addition, Example 5 with the addition of the expanding agent achieves a 24-hour free expansion rate of 0.25%, effectively compensating for shrinkage; Example 6 with the incorporation of the defoaming agent has an air content reduced to 1.5%, the paste is more dense, and the 28-day compressive strength is increased to 84.2 MPa, proving that the functional components of the present application can further expand the performance of the paste.
[0098] In addition, as can be seen from the data in Table 2, Comparative Example 1 uses ordinary bentonite with a low CEC value and without modification, and even if the amount added is 1.5 parts, it is still difficult to effectively stabilize the paste, ultimately resulting in a relatively high bleeding rate of the paste, and the strength performance is also relatively low. Comparative Example 2 uses a polyacrylamide organic thickening agent, which can adjust the performance of the paste to some extent, but has obvious defects: the paste loses fluidity too quickly and gels within 60 minutes, which cannot meet the requirements of actual construction for the working performance of the paste. Comparative Example 3 lacks the cooperation and support between components due to the lack of any synergistic system, resulting in poor performance in the three key indicators of paste fluidity, system stability, and final strength.
[0099] The results of the above multiple comparison experiments fully prove that the "nanosol-high CEC layered silicate clay" synergistic system constructed by the present application can effectively compensate for the performance defects of single components or non-synergistic systems, and provides key support for the balance between fluidity, stability, and strength of the paste, which is the core to ensure that the paste meets the requirements of construction and use.
[0100] Finally, it should be noted that: the above examples are only preferred embodiments of the present application, mainly for explaining the technical solutions of the present application, but not limiting the present application, and more not for limiting the patent protection scope of the present application. Any modification or adjustment based on the main design idea and core spirit of the present application without substantial difference, if the technical problems solved are consistent with the present application, should still be included in the protection scope of the present application; in addition, the direct or indirect application of the technical solutions of the present application to other related technical fields should also be included in the patent protection scope of the present application.
Claims
1. A high-flowability grouting material, characterized in that, The raw materials include the following components in parts by weight: 40-60 parts silicate cement, 20-30 parts ultrafine mineral powder, 5-8 parts nano sol, 1-3 parts sodium-modified layered silicate clay or synthetic lithium saponite, and 0.5-1.2 parts polycarboxylate superplasticizer; the water-cement ratio of the grouting material is 0.17-0.19, preferably 0.
18.
2. The ultra-high fluidity grouting material according to claim 1, characterized in that, Its raw materials include the following components in parts by weight: 45-50 parts silicate cement, 25-30 parts ultrafine mineral powder, 6-7 parts nano sol, 1-3 parts sodium-modified layered silicate clay or synthetic lithium saponite, and 0.5-1.2 parts polycarboxylate superplasticizer.
3. A high-flowability grouting material according to claim 1 or 2, characterized in that, The silicate cement is P.II 52.5 grade or P.O 52.5 grade silicate cement; And / or the specific surface area of the ultrafine mineral powder is ≥1000 m². 2 / kg; preferably, the super mineral powder is S105 grade ultrafine mineral powder; And / or the nanosol includes at least one of silica sol, aluminum sol, and titanium sol; Preferably, the SiO2 content in the silica sol is 30±2wt%, and the particle size is 5-10nm; The aluminum sol contains 18-22 wt% Al2O3 and has a particle size of 15-25 nm. The titanium sol contains 25-30 wt% TiO2 and has a particle size of 8-15 nm.
4. A high-flowability grouting material according to claim 1 or 2, characterized in that, The sodium-modified layered silicate clay is prepared by reacting layered silicate clay with sodium salt solution under heating conditions; Preferably, the modification method of sodium-modified layered silicate clay includes the following steps: mixing layered silicate clay with sodium salt solution, placing it in a reaction vessel, heating and stirring at 60-90°C, and simultaneously mechanically grinding it with a high-speed grinder for 30-60 minutes; after the reaction is completed, filtering, washing until the pH of the filtrate is 7-8, drying, and pulverizing to obtain sodium-modified layered silicate clay; Preferably, the layered silicate clay includes at least one of lithium montmorillonite and saponite; Preferably, the sodium salt solution includes at least one of Na2CO3, NaCl, and Na2SiO3, with a mass concentration of 3-8%, and the solid-liquid ratio of layered silicate clay to sodium salt solution is 1:3-1:
5.
5. A high-flowability grouting material according to claim 1 or 2, characterized in that, The grouting material also includes a defoamer comprising 0.01-0.1% of the total weight of the grouting material; Preferably, the defoamer includes polyoxypropylene polyoxyethylene ether or silicone defoamer.
6. A high-flowability grouting material according to claim 1 or 2, characterized in that, The grouting material also includes calcium sulfoaluminate-based expanding agent accounting for 0.5-2% of the total weight of the grouting material; Preferably, the specific surface area of the calcium sulfoaluminate-based expanding agent is 400-500 m² / kg.
7. The method for preparing ultra-high fluidity grout according to any one of claims 1-6, characterized in that, Includes the following steps: S1. Preparation of premixed dry powder: Weigh each powdered material according to the ratio, stir, mix evenly to obtain premixed dry powder; the powdered material includes silicate cement, ultrafine mineral powder, sodium-modified layered silicate clay, polycarboxylate superplasticizer, preferably, it also includes calcium sulfoaluminate expansive agent; S2. Preparation of mixing solution containing nano-sol: Calculate the required amount of mixing water based on the water-cement ratio of the grout, then weigh out the nano-sol in the corresponding proportion and add it to the mixing water, stir, so that the nano-sol is evenly dispersed in the water to form a stable mixing solution containing nano-sol; Preferably, the defoamer and the nano-sol are stirred together; S3. Mix the premixed dry powder with the mixing liquid containing nano-sol evenly to obtain ultra-high fluidity grout.
8. The method for preparing the ultra-high fluidity slurry according to claim 7, characterized in that, In step S1, the powdered materials are stirred at a speed of 300-500 r / min for 20-40 minutes, preferably in a twin-shaft mixer. In step S2, the mixture is stirred for 10-15 minutes at a speed of 500-800 r / min using a magnetic stirrer.
9. The method for preparing ultra-high fluidity slurry according to claim 7, characterized in that, In step S3, the premixed dry powder and the mixture containing nano-sol are first stirred at low speed and then stirred at high speed; preferably, the mixture is stirred at 140±5r / min for 1-2 minutes and then at 285±10r / min for 2-3 minutes.
10. The application of the ultra-high fluidity grouting material according to any one of claims 1-6, characterized in that, Application in grouting of ducts in post-tensioned prestressed structures.